Analysis Of Radiation Dose In Women's Reproductive Organs In Diagnosis Support Histerosalfingografi As The Radiation Safety Unit Radiology Service - Darmini Darmini; Siti Masrochah; Siti Daryati (Jurnal LINK, 2013)
A study concerning the analysis of Radiation Dose in Female Reproductive Organs In Examination Hysterosalpingography For Supporting safety Radiation In Radiology Services Unit. The purpose of this study to obtain descriptions of the radiation dose received by the reproductive organs at Hysterosalpingography examination and find out how much the level of safety obtained by the reproductive organs of the risk of biological effects on Hysterosalpingography examination. This research is a quantitative approach to measuring radiation. Amount sample used in this study was performed in 6 patients and Maternity Hospital Semarang. This source obtained using TLD dosimeters chips are placed on the patient's skin surface in mid gonads, right and left ovaries. The value of radiation dose TLD reader reading results are recorded in the tabulation of the radiation dose to the HSG examination. Furthermore, the total value obtained by comparison with a reference standard performed as recommended by BAPETEN that the reference dose on pelvic examination should not be more than 10 mGy. The results showed that the dose of radiation received by the reproductive organs on Hysterosalpingography examination based on exposure factors, the greater the voltage of the tube then the average absorbed dose greater, based on the thickness of the thicker body of the patient's body absorbed dose average lower, receiving total dose accepted patients receiving the lowest dose of 1 x ekposi 1.508 mGy, the highest 2.341 mGy. For patients receiving the lowest dose of 2 x eksposi 3,016 mGy, the highest 4,682 mGy. The level of security is obtained against the risk of reproductive organs of biological effects on the examination Hysterosalpingography is still in the safe level for the highest total dose received was 4,682 mGy (below 10 mGy).